Myopia: An alarming situation in near future - Ashraf Ali; Humayoun, Aroosa (Journal of the Pakistan Medical Association, 2023)
Madam, I am writing to draw attention to an issue that I believe is of great concern for our society: the alarming increase in cases of myopia due to excessive near work. Myopia, or nearsightedness, when the eye has difficulty focusing on distant objects. The prevalence of myopia has been increasing rapidly worldwide, particularly in Asia, where it is estimated that up to 80% of young adults are affected. In the United States, the prevalence of myopia has doubled in the past 30 years.[1] One major factor contributing to this increase is the growing amount of time people spend near work, such as reading, using computers, and playing video games. This kind of work requires the eyes to focus on close objects for extended periods, which can cause the eye to elongate and result in myopia. The consequences of myopia are not only visual but also have significant impacts on quality of life. Myopia increases the risk of eye diseases such as glaucoma, cataracts, and retinal detachment, which can lead to blindness. It can also have a negative impact on academic and career opportunities, as well as physical and social activities. [2] Get regular eye exams: Regular eye exams are crucial for detecting myopia early and monitoring its progression. It is recommended that infants have their first eye exam at six months, and then again at the ages of three and five, and every two years after that. Adults should have an eye exam at least once every two years, or more frequently if advised by their eye doctor. Practice good visual habits: Good visual habits can help prevent myopia from worsening. This includes taking frequent breaks when reading or using electronic devices, maintaining a comfortable distance from the screen, and practicing good posture. You can also try doing eye exercises to strengthen your eye muscles. Spend time outdoors: Studies have shown that spending time outdoors, especially in natural light, can help prevent the onset and progression of myopia in children. Aim for at least 2 hours of outdoor time per day. A study by David A Wilson et al. showed that by 2050 there will be 1 billion people with myopia.[3] Nowadays, our young generation is executively using smartphones and digital screens. All ophthalmologist and optometrist are advised to know all the clints regarding close work to rest in between your work. —Continue